Occurrence of Bisphenol A, Estrone, 17β-Estradiol and 17α-Ethinylestradiol in Portuguese Rivers - Rocha, Sónia (2013)
This study focused on the occurrence of several EDCs including bisphenol A, estrone (E1), the 17b-estradiol (E2) and 17a-ethinylestradiol (EE2) in fourteen rivers of Portugal. Samples analysis revealed a widespread contamination of BPA especially in Ave, Ca´vado, Douro, Ferro, Sousa and Vizela Rivers. Achieving 98.4 ng/L for the highest concentration. The estrogens achieved above the method quantification limit (MQL) were E1 in A ´ gueda River and E2 in Ave, Lima and Taˆmega Rivers. The maximum concentration detected for E1 was 26.9 ng/L. EE2 was detected only below MQL.